Congenital coronary artery cardiac chamber fistula - Olguntürk, Rana; Özme, Şencan; Bilgiç, Arman; Ekici, Enver (The Turkish Journal of Pediatrics, 1980)
Four cases of coronary arteriovenous fistula are reported with a brief review of the literature. Differentiation of this condition from patent ductus arteriosus on the basis of the murmur characteristics and location was discussed. Retrograde aortagraphy was found to be the best diagnostic method. Early correction should be carried out to prevent complications. Both pre and post-operative antibiotic prophylaxis are advisable to prevent subacute bacterial endocarditis.